2016
DOI: 10.1021/acs.jproteome.5b01149
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Unveils Fibroblast–Cardiomyocyte Lactate Shuttle and Hexokinase Paradox in Mouse Muscles

Abstract: Quantitative mapping, given in biochemically interpretable units such as mol per mg of total protein, of tissue-specific proteomes is prerequisite for the analysis of any process in cells. We applied label- and standard-free proteomics to characterize three types of striated muscles: white, red, and cardiac muscle. The analysis presented here uncovers several unexpected and novel features of striated muscles. In addition to differences in protein expression levels, the three muscle types substantially differ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Together, the alteration in the cellular levels of the three proteins strongly support the hypothesis that the fibroblasts growing in the presence of cancer cells, and presumably also some other cell types (e.g., cardiomyocytes [25]), start to produce lactate while the capacity of cancer cells (and other cells which accompany fibroblasts) to produce lactate is significantly reduced.…”
Section: Resultssupporting
confidence: 63%
“…Together, the alteration in the cellular levels of the three proteins strongly support the hypothesis that the fibroblasts growing in the presence of cancer cells, and presumably also some other cell types (e.g., cardiomyocytes [25]), start to produce lactate while the capacity of cancer cells (and other cells which accompany fibroblasts) to produce lactate is significantly reduced.…”
Section: Resultssupporting
confidence: 63%
“…We calculated an approximate total protein content of 1 ng per diploid nucleus and found that a heart cavity muscle cell has an approximate volume of 5 pL per nucleus (note that about 30% of all cardiomyocytes have two or more nuclei 2 ). These values are roughly double that of mouse heart muscle cells 30 . Estimated protein copy numbers per diploid nucleus and protein concentration 31 across our samples ranged from ~10 to 10 9 and <0.1 nM to 200 µM, respectively (Supplementary Data 3 ).…”
Section: Resultsmentioning
confidence: 72%
“…However, we found that the molar ratio of Pyg to Gys (a glycogen degradation to glycogen synthesis enzyme) in hippocampus is very high and similar as in white skeletal muscle fibers (Rakus, Gizak, & Wiśniewski, ), which are suited for the rapid glycogen degradation. This suggests that episodes of glycogen degradation in astrocytes are rapid and thus, the short‐time local increase in lactate may be sufficient to stimulate neuronal energy production in OXPHOS.…”
Section: Discussionmentioning
confidence: 77%
“…However, we found that the molar ratio of Pyg to Gys (a glycogen degradation to glycogen synthesis enzyme) in hippocampus is very high and similar as in white skeletal muscle fibers (Rakus, Gizak, & Wi sniewski, 2016), which are suited for the rapid glycogen degradation.…”
Section: Discussionmentioning
confidence: 78%